EVALUATION OF TPPAS REGIONAL NAMBO DEVELOPMENT PLAN - NAJLA NADHIA RAHMAWATI (NIM: 15312011),
Cipayung and Galuga final disposal experiencing overcapacity because of the increased amount of solid waste input. West Java Provincial Government will establish Regional TPPAS Nambo as a solution to these problems. This study presents some related data about generation, composition and characteristics of the waste that goes to Cipayung final disposal from Depok City and Galuga final disposal from Bogor City and Bogor Regency, to check their compatibility with the planned waste management in TPPAS Nambo. Generation recording performed for 8 consecutive days, and the composition of waste had been done according to SNI 19-3794-1994. Characteristics analysis include: examination of moisture content, volatile matter, fixed carbon, ash content and calorific value. Obtained average waste generation of Depok City, Bogor City and Bogor Regency are 601 tons/day, 794 tons/day, and 509 tons/day. The average composition of the waste is dominated by organic waste (49.4%), indicating a good potential for waste to be processed with the help of microorganisms. The next large percentage are plastic (19.83%), paper (15.29%), textiles (2.24%), wood (1.26%) and rubber (0.08%) which can be categorized into combustible and recyclable material, so it can be used as RDF. Metal (0.31%) and glass (0.15%) can only be recycled and can not get into the cement kiln. It also apply to hazardous waste (10.52%) and others (0.94%) consisting of stone, sand, and gravel, so it can not be used as RDF. Based on the laboratorium analysis the moisture content of waste obtained 72%. Therefore pre treatment of solid waste is needed in order to reduce the moisture contents. In addition, the calorific value obtained at 1451 kcal / kg have met the standard RDF for cement industry in Indonesia. Based on projections, it was found that the amount of solid waste from all three areas will exceed the allowed quantity of waste input from BPSR West Java. Hence the need for other strategies on waste management in the three regions to reduce the amount of waste that must be addressed.